In vivo cartilage deformation after different types of activity and its dependence on physical training status. Issue 2 (12th January 2005) - Eckstein, F; Lemberger, B; Gratzke, C; Hudelmaier, M; Glaser, C; Englmeier, K-H; Reiser, M
Abstract : Background: Knowledge of the deformational behaviour of articular cartilage in vivo is required to understand the pathogenesis of osteoarthritis and the mechanical target environment of prospective cartilage transplant recipients. Objectives: To study the in vivo deformational behaviour of patellar and femorotibial cartilage for different types of physiological activities; and to test the hypothesis that in vivo deformation of cartilage is modified by intense physical exercise. Methods: Magnetic resonance imaging and 3D digital image analysis were used to determine cartilage volume before and after physical activity in the patella of 12 volunteers (knee bends, squatting, normal gait, running, cycling). Deformation of femorotibial cartilage was investigated in 10 subjects (knee bends, static compression, high impact loading). Patellar cartilage deformation after knee bends was compared in seven professional weight lifters, seven sprinters, and 14 untrained volunteers. Results: Patellar cartilage deformation was −5.9% after knee bends, −4.7% after squatting, −2.8% after normal walking, −5.0% after running, and −4.5% after cycling. The pattern of patellar cartilage deformation corresponded to the range of motion involved in the particular activity. Tibial cartilage deformation was greatest under high impact loading (−7%), but small for other activities. No significant difference was found between athletes and non-athletic controls. Conclusions: Patellar cartilage deformation shows a "dose dependent" response, where more intense loading leads to greater deformation. Relatively little deformation was observed in the femorotibial joint, except during high impact activities. The findings provide no evidence that adult human cartilage properties are amendable to training effects in vivo.